2020
DOI: 10.1016/j.jum.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 impact on urban mobility

Abstract: This paper presents individuals' adjustment in daily out-of-home travel activities, in-home activities, and long-distance travel during the COVID – 19 travel restrictions. This study utilizes data from the COVID – 19 Survey for assessing Travel impact (COST) for the Kelowna region of British Columbia, Canada. The analysis suggests that individuals' participation in out-of-home activities were reduced by more than 50% during COVID – 19. The highest daily frequency of travel is found for routine shopping, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 1 publication
2
78
1
9
Order By: Relevance
“…A similar trend was noticed during the outbreak of SARS and there was a significant reduction in leisure-based travel demand due to internal motivations (e.g., risk perception) and external enforced measures (e.g., travel restrictions, imposing of stay-at-home) ( Wen et al, 2005 ). On contrary, a higher frequency of travel related to routine shopping was noticed during the early days of the COVID-19 outbreak ( Fatmi, 2020 ). However, ( Friman et al, 2017 ) found that critical or unexpected incidences during travel can change mood immediately, indirectly impacting travel satisfaction.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…A similar trend was noticed during the outbreak of SARS and there was a significant reduction in leisure-based travel demand due to internal motivations (e.g., risk perception) and external enforced measures (e.g., travel restrictions, imposing of stay-at-home) ( Wen et al, 2005 ). On contrary, a higher frequency of travel related to routine shopping was noticed during the early days of the COVID-19 outbreak ( Fatmi, 2020 ). However, ( Friman et al, 2017 ) found that critical or unexpected incidences during travel can change mood immediately, indirectly impacting travel satisfaction.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The validated sample size is 202, however, due to multiple engagements in out-of-home travel activity in a day total response of 226 was retained for travel satisfaction. Detailed survey information can be found elsewhere ( Fatmi, 2020 ). Table 1 shows the variables used in this model and descriptive statistics for each.…”
Section: Data Used In the Empirical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last year of 2020, many studies were carried out regarding the COVID-19 pandemic. For instance, several studies have focused on the influences of COVID-19 outbreak on the urban activities, systems, processes, and health (e.g., Chapman & Tsuji, 2020 ; Fatmi, 2020 ; Feng et al, 2020 ; Girdhar et al, 2020 ). In the vice versa, some scholars have addressed the possible links between urban air pollution and illness outbreaks in the different regions and countries (e.g., Conticini et al, 2020 ; Magazzino et al, 2020 ; Ogen, 2020 ; Travaglio et al, 2020 ; Yongjian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…19 Overall, individuals made about 1.62 trips/day/person during COVID-19 compared to about 3.33 trips/day/person in the pre-pandemic period, which is down more than 50%. 20 For residential, we found negative correlation to cumulative case of COVID-19. Residential indicates how long an individual stay within nonpublic places such as home,etc.…”
Section: Discussionmentioning
confidence: 68%